Calcium Mediated Cold Acclimation in Plants: Underlying Signaling and Molecular Mechanisms - Iqbal, Zahra; Memon, Anjuman Gul; Ahmad, Ausaf; Iqbal, Mohammed Shariq (Frontiers in Plant Science, 2022)
Exposure of plants to low temperatures adversely affects plant growth, development, and productivity. Plant response to cold stress is an intricate process that involves the orchestration of various physiological, signaling, biochemical, and molecular pathways. Calcium (Ca2+) signaling plays a crucial role in the acquisition of cold stress. Upon perception of cold stress, Ca2+ channels and/or Ca2+ pumps are activated which induces the Ca2+ signatures in plant cells. The Ca2+ signatures spatially and temporally act inside a plant cell and are eventually decoded by specific Ca2+ sensors. This series of events results in the molecular regulation of several transcription factors (TFs), leading to downstream gene expression and withdrawal of an appropriate response by the plant. In this context, calmodulin binding transcription activators (CAMTAs) constitute a group of TFs that regulate plant cold stress responses in a Ca2+ dependent manner. The present review provides a catalog of the recent progress made in comprehending the Ca2+ mediated cold acclimation in plants.